PERAN PENDIDIKAN ISLAM TERHADAP PETUMBUHAN EKONOMI - Zubairi, Zubairi; Musthofa, Musthofa; Nur Khofifah, Siti (STAI Asy-Syukriyyah, 2024)
The influence of the quality of Islamic education in Indonesia also influences the development of economic growth. Therefore, the importance of economics for the development of Islamic education in Indonesia is by increasing learning productivity so that the nation's future generations who are still studying can better understand the science of Islamic education and can improve it for the advancement of Islamic education in Indonesia. With economic needs increasing day by day, it is the Islamic education factor that will help economic growth, because with Islamic education it will produce more professional qualities of Human Resources (HR) both for the industrial sector and other sectors, and from there it will have an impact and influence on the future economic growth of the Indonesian nation.